Indicadores de sostenibilidad ambiental - Rey Mejías, Concepción (Observatorio Medioambiental, 2002)
Increase in production as measured in national income is generally called economic growth, identified with an increase in welfare an conveived as the indicator from economic success. All countries of world give it the highest priority in their economic policy. At the same time, the present increases in national income are being accompanied by destruction of the environment. It is necesary consider the trouble of scarce resources at man’s disponsal. This text will 1) Outline information which should be included when national accounts are published in order to avoid misinterpretation of the changes in the level of national income by politicians and the public; 2) Examine whether it is possible to correct national income for environmental losses; 3) Propose a parctical and defensible solution for this problem; 5) Sum up advantages and disadvantages of this solution.
Keywords: Economic growth; enviroment destruction; indicators; National Income